APPLICATION OF TIE-DYE AND MACHINE EMBROIDERY WITH NATURAL DYE AS NEO-MEDIEVAL THEMED FASHION PRODUCTS - Embun Ayu Winasis, Titis
Referring on how sense of fashion and consumerism has escalated in Indonesia, especially how the value of art from handmade products has offered so much for public now, the role of designers is not only to create, but to evolve as educators, facillitators, and activists through their designs. Tie-dye is a democratic medium, the textiles has been worn by the elites to represents their wealth, it as well has been used by the wider public. The design also involves machine embroidery technique that requires carefulness and patience. The process will use natural dye from sappanwood bark, mangrove trees bark, mango leaves, and avocado seed that are rich in a sense of local wisdom. Moreover the growth of economy has influence styles on how designers’ process leaves mark in their market, hence the design process seek a deeper level from the vision of Indonesia Trend Forecasting (ITF) that analyzes various culture, nations, and the people from vast disciplines to see the direction of deliberation that transforms one trend to another ones. The apprehending of the history of deliberation that evolutionize social-culture could be used as a recipe to predict future trends through Neo-Medieval; a Romantism of Neo-mediveal, a theme inspired by Hedley Bull in 1977 in “Anarchical Society: A Study of Order in World Politics, to depict the begone power of governance in contemporary world. The design will revoke on how these techniques can be tranforms to products that are armory, wild, elegant, and intellectual. This deluxe Ready-To-Wear product will revive the essence of fashion that is elegant, owning a sense of flexibility such as jacket, draped textiles, sarong, pants, skirts, and other fashion assesorizes.